Exceptional preservation of cells in phosphate and the early evolution of the biosphere - Battison, L (2012)
The Proterozoic period saw some of the most fundamental revolutions in the biological and geological world. During this period, life diversified and set the stage for the radiation of multicellular life, altering the face of the planet in the process. The fossil record of this time is not yet fully understood, and a revisitation of a historically reported fossil deposit in the 1 Ga Torridon rocks of northwest Scotland shows that they host the fossils of the earliest non-marine eukaryotes, as well as a full and diverse fossil assemblage preserved in sedimentary phosphates and shales. Fine scale sedimentology of the fluvio-lacustrine rocks of the Torridon Group reveals them to be laid down in a laterally variable basin with distinctly different palaeoenvironments. The resident biota is seen to be similarly variable between lithofacies. New criteria for classifying taphonomic effects are presented, and used to characterise assemblages from different palaeoenvironments, with broader applications beyond this study. The Torridon rocks are also host to macrostructures on the surfaces and soles of beds, and these are interpreted as of likely biological origin, with their variability mapped between different lithofacies. High-resolution studies of both the preserved biota and the mineralogy of the preserving medium reveal in detail not only the fine scale structure of the fossil organisms, but also the reasons for their exceptional preservation. Phosphate is analysed in detail to explain its enigmatic occurrence in Proterozoic lakes. To place the Torridon deposits in context, both older and younger rocks were examined in comparison, from the 2 Ga Gunflint Formation of Ontario, Canada, and the Precambrian-Cambrian successions of eastern Newfoundland respectively. New finds of phosphate in these rocks help to reveal biochemical interactions and evolution on the early Earth, with implications for further understanding life on our own planet and elsewhere.